(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
An ambitious programme of economic reforms and anti-corruption measures has been undertaken by President Xi Jinping, along with a large-scale transformation of Chinese diplomacy. His foreign policy doctrine highlights the defence of sovereignty interests and the development of the country’s military capacities, with Asia currently constituting its essential strategic priority. This is reflected in various regional integration initiatives linking security and economic development, whereby Beijing is proactively pushing for a rearrangement of regional order, redefining Asia as a geopolitical space with important repercussions for global equilibrium